Missing Sam : a novel - Umrigar, Thrity N. (Algonquin Books of Chapel Hill/Little, Brown and Company, a Hachette Book Group, 2026)
"One night after a party, old grievances surface between married couple Aliya and Sam and the night ends badly with a heated argument. Sam goes for a run early the next morning to clear her head--and doesn't come back. Aliya reports her wife missing, but as a gay, Muslim daughter of immigrants, she can't escape the scrutiny and suspicion of those around her. Scared and furious and feeling isolated as strangers and acquaintances alike doubt her innocence, Aliya makes one wrong choice after another. She must fight to prove her innocence in the public eye even as she is torn between her fear that Sam is dead and her desire to find and save her wife. But is safety ever truly possible for them?" --